2020
DOI: 10.3390/en13082115
|View full text |Cite
|
Sign up to set email alerts
|

Future Design Approaches for Energy Poverty: Users Profiling and Services for No-Vulnerable Condition

Abstract: Analyzing data from the Energy Poverty Observatory in Europe, it emerges that more than 50 million households in the EU live in energy poverty (people that cannot heat their homes during winter; cannot make their homes comfortable during the summer; pay their energy bills late). Research studies realized in the last 20 years highlight that making energy demand efficient and effective is the more significant and socially important the more it is able to involve users who are unable to sustain energy demand. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Furthermore, and consistent with the study of Uhr, Chagas and Uhr 2019, family income was positively related to consumption, while the tariff presented a negative impact on the electricity consumption. This latest study also found that the raise in tariff affects households with low electricity consumption leading to a great restriction in consumption, situation that is in line with the concept of energy poverty (BOERI et al, 2020). Abrahão and Souza ([2021]) also raised public policies and programs implemented from the year of 2000 verifying diversified regional responses in the residential electricity consumption.…”
Section: The Brazilian Residential Sectormentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, and consistent with the study of Uhr, Chagas and Uhr 2019, family income was positively related to consumption, while the tariff presented a negative impact on the electricity consumption. This latest study also found that the raise in tariff affects households with low electricity consumption leading to a great restriction in consumption, situation that is in line with the concept of energy poverty (BOERI et al, 2020). Abrahão and Souza ([2021]) also raised public policies and programs implemented from the year of 2000 verifying diversified regional responses in the residential electricity consumption.…”
Section: The Brazilian Residential Sectormentioning
confidence: 56%
“…Household income and regionality were identified as relevant aspects of influence over consumption, recommending that there should be a review of these aspects in energy policy. Therefore, it is reasonable to assume that electricity consumption indices should be different for Brazilian regions, as well as for population age groups, since culture, household income and lifestyle are variables that impact the patterns of electricity consumption differently (ABRAHÃO; SOUZA, [2021];BOERI et al, 2020;ESTIRI;ZAGHENI, 2019;LIDDLE, 2014;TSO;GUAN, 2014;; LINS, 2010;; O'NEIL;CHEN, 2002).…”
Section: The Brazilian Residential Sectormentioning
confidence: 99%
“…Putting RE technologies in good use in the context of Energy Communities, people have the chance to observe, appreciate and hopefully adopt good practices and behavior. Last but not least, RECs can have a very important role in the alleviation of energy poverty [36]. Either as a vulnerable individual/group or as a pro-active energy user, REC members have the opportunity to produce, store, use and generally manage energy in a way that its distribution becomes more accessible and socially just.…”
Section: Portugalmentioning
confidence: 99%
“…In an attempt to face energy poverty, following the 2008 turmoil, and to meet EU's energy efficiency targets, Greece's Ministry of Environment and Energy, on January 2018, presented L.4513/2018, on energy communities (EC) [36]. The Ministry's proposed law, was voted by a majority decision and its main purpose was to establish the legal foundation for a civil cooperative on the energy sector, especially regarding local production and consumption of energy [37,38].…”
Section: Social Housing and Energy Communities In Greecementioning
confidence: 99%
“…There are some remarkable studies reviewing the energy poverty literature [3,4,13,20,[31][32][33][34], but none of them performed a scientometric analysis to reveal networks among publications in terms of global and local citation counts, citing and cited references, co-citation, bibliographic coupling, co-authorship, and co-occurrence. Moreover, the network analysis in this study is based on a larger and more comprehensive dataset covering all information on energy poverty studies, stored in the Web of Science.…”
Section: Introductionmentioning
confidence: 99%